1993
DOI: 10.1007/bf00202078
|View full text |Cite
|
Sign up to set email alerts
|

Ozone uptake in the sun and shade crown of spruce: quantifying the physiological effects of ozone exposure

Abstract: Summary. The uptake of air pollutants depends both on pollutant concentration and on stomatal conductance. This paper deals with the uptake of ozone (03) from the air into the needles of Norway spruce [Picea abies (L.) Karst.] under ambient climatic conditions. Regulation of 03 uptake by the stomata is shown and also the difference b~-tween the "physiologically active 03 concentration" and the 03 concentration of the ambient air. Data from the sun and shade crown of spruce trees at 1000 m a. s. 1. are presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
30
1
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(38 citation statements)
references
References 28 publications
6
30
1
1
Order By: Relevance
“…Similar results were obtained for Larix decidua (Wieser, 2002), Picea abies (Dobson et al, 1990;Polle et al, 1995;Wieser and Havranek, 1993) and Populus spp. (Wang et al, 1995).…”
Section: Assessment Of Ozone Uptake At the Leaf Levelsupporting
confidence: 77%
“…Similar results were obtained for Larix decidua (Wieser, 2002), Picea abies (Dobson et al, 1990;Polle et al, 1995;Wieser and Havranek, 1993) and Populus spp. (Wang et al, 1995).…”
Section: Assessment Of Ozone Uptake At the Leaf Levelsupporting
confidence: 77%
“…However, when absorbed, it decomposes extremely rapidly. At [O^\ 0 nPa Pa"\ calculated O3 uptake by spruce needles and measured O.j uptake rates match closely (Wieser & Havranek, 1993;Polle, Wieser & Havranek 1995). In contrast to SO^ and O3, intercellular concentrations of NO2 and NO are distinctly greater than zero.…”
Section: Intercellular Trace Gas Concentrations I\gas]^)supporting
confidence: 53%
“…Duyzer et al (1995) showed that the sensitivity of stomatal conductance to water vapour pressure deficit (VPD) was crucial to modelling O $ flux to a coniferous forest. Wieser & Havranek, (1993, 1995 found that VPD was the climatic factor most closely correlated with ambient O $ concentration. Thus, when O $ concentrations were highest, the flux tended to be restricted by stomatal narrowing.…”
Section:     mentioning
confidence: 99%